Study on the Regulated Cell Death of Hypertrophic H9c2 Cells Induced by Au:Ag Nanoparticles - Galindo-Padrón AG; Lorenzo-Anota HY; Rueda-Munguía M; García-Carrasco A; Gaitán López M; Vázquez-Garza E; Campos-González E; Lozano O; Cholula-Díaz JL (International Journal of Nanomedicine)
Andrés G Galindo-Padrón,1,* Helen Yarimet Lorenzo-Anota,2,3,* Mayte Rueda-Munguía,2,3 Alejandra García-Carrasco,1 Mabel Gaitán López,1 Eduardo Vázquez-Garza,2 Enrique Campos-González,4 Omar Lozano,2,3,5 Jorge L Cholula-Díaz1 1School of Engineering and Sciences, Tecnologico de Monterrey, Monterrey, Nuevo Leon, Mexico; 2Institute for Obesity Research, Tecnologico de Monterrey, Monterrey, Nuevo Leon, Mexico; 3School of Medicine and Health Sciences, Tecnologico de Monterrey, Monterrey, Nuevo Leon, Mexico; 4Departamento de Física, Instituto Nacional de Investigaciones Nucleares, Ocoyoacac, Mexico; 5Cátedra de Cardiología y Medicina Vascular, Tecnologico de Monterrey, Monterrey, Nuevo León, México*These authors contributed equally to this workCorrespondence: Omar Lozano; Jorge L Cholula-Díaz, Email omar.lozano@tec.mx; jorgeluis.cholula@tec.mxBackground and Aim: Over the past years, noble metal-based nanoparticles have been extensively investigated for their applications in nanomedicine. However, there are still concerns about the potential adversities that these nanoparticles may present in an organism. In particular, whether they could cause an exacerbated cytotoxic response in susceptible tissues due to damage or disease, such as the heart, liver, spleen, or kidneys. In this regard, this study aims to evaluate the cytotoxicity of mono- and bimetallic nanoparticles of gold and silver (Au:Ag NPs) on healthy and hypertrophic cardiac H9c2 cells, and on healthy and metabolically activated macrophages derived from U937 cells. The main objective of this work is to explore the susceptibility of cells due to exposure to Au:Ag NPs in conditions representing cardiometabolic diseases.Methods: Au:Ag NPs were synthesized in different molar ratios (Au:Ag, 100:0, 75:25, 50:50, 25:75, 0:100) using starch as a capping and reducing agent. Their physicochemical properties were characterized through UV-vis spectroscopy, X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, dynamic light scattering (DLS), ζ-potential measurements, and transmission electron microscopy (TEM). Moreover, the effect of the metal-based nanoparticle exposure on healthy and hypertrophic H9c2 cells was measured by analyzing the cellular vitality, the loss of mitochondrial membrane potential (∆Ψm), and the production of mitochondrial reactive oxygen species (mROS).Results: The Au:Ag NPs did not affect the cell vitality of healthy or metabolically activated macrophages. On the contrary, healthy H9c2 cells showed decreased mitochondrial metabolism when exposed to NPs with higher Ag concentrations. Furthermore, hypertrophic H9c2 cells were more susceptible to the same NPs compared to their non-hypertrophic counterparts, and presented a pronounced loss of ∆Ψm. In addition, these NPs increased the production of mROS and regulated cell death in both cardiac cells.Conclusion: In conclusion, low doses of high-Ag load in Au:Ag NPs produced cytotoxicity on H9c2 cardiac cells, with hypertrophic cells being more susceptible. These results suggest that cardiac hypertrophic conditions are more prone to a cytotoxic response in the presence of bimetallic Au:Ag NPs compared to healthy cells. In addition, this work opens the door to explore the nanotoxicity of noble metal-based NPs in biological disease conditions.Keywords: cardiovascular disease, hypertrophic cardiomyoblasts, bimetallic nanoparticles, metabolically activated macrophages